Eksistensi layanan drive thru di perpustakaan perguruan tinggi pada era new normal - Rahmawati, Nadia Rifka; Masruri, Anis (Daluang: Journal of Library and Information Science, 2023)
Introduction. Library services during the Covid-19 pandemic have decreased even to the point that services are completely closed. This happens because the virus is easily spread through the air, causing limited community activities outside the home. To overcome this problem, the library provides service innovations that can be used during a pandemic, namely drive thru services. The purpose of this study is to describe the existence of libraries in the new normal era so that many libraries adopt drive thru services. Methodology. The method used in this research is a library research method with a qualitative approach. Library research technique is a technique that takes data sources in the form of books as the object of study. Results and discussion. This drive-thru service adopts fast food franchise services. This service became an innovation and alternative service when the COVID-19 pandemic entered Indonesia. To maintain the existence of the library finally, innovate to provide this service. This service is considered effective because of the lack of direct physical contact with other people in addition to reducing the crowding and spread of the covid-19 virus. Conclusion. Currently, the pandemic has begun to recede. But that doesn't detract from drive thru service. In this new normal era, drive thru services should increasingly exist and improve this drive thru service to provide better and better service.